2018
DOI: 10.1186/s13287-018-0834-0
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human pluripotent stem cells into two distinct NKX6.1 populations of pancreatic progenitors

Abstract: BackgroundThe expression of a specific combination of transcription factors (TFs) in the multipotent progenitor cells (MPCs) is critical for determining pancreatic cell fate. NKX6.1 expression in PDX1+ MPCs is required for functional β cell generation. We have recently demonstrated the generation of a novel population of human pluripotent stem cell (hPSC)-derived MPCs that exclusively express NKX6.1, independently of PDX1 (PDX1−/NKX6.1+). Therefore, the aim of this study was to characterize this novel populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 46 publications
(74 reference statements)
1
41
1
Order By: Relevance
“…Definitive endoderm is the common progenitor to epithelial cells in diverse internal organs, including the liver, pancreas and intestines (Tremblay and Zaret, 2005). To examine their multilineage differentiation potential, we cultured hEPCs in pancreatic (Aigha et al, 2018) or intestinal (Spence et al, 2011) induction medium for four days and then evaluated the cells for expression of pancreatic lineage-specific transcription factors pancreatic and duodenal homeobox1 (PDX1) (Offield et al, 1996) and caudal type homeobox 2 (CDX2), a member of the caudal-related homeobox transcription factor gene family. CDX2 is a major regulator of intestine-specific genes involved in cell growth and differentiation (Gao et al, 2009).…”
Section: Results Hepcs Induced By Chir-99021 Possess Multilineage Difmentioning
confidence: 99%
“…Definitive endoderm is the common progenitor to epithelial cells in diverse internal organs, including the liver, pancreas and intestines (Tremblay and Zaret, 2005). To examine their multilineage differentiation potential, we cultured hEPCs in pancreatic (Aigha et al, 2018) or intestinal (Spence et al, 2011) induction medium for four days and then evaluated the cells for expression of pancreatic lineage-specific transcription factors pancreatic and duodenal homeobox1 (PDX1) (Offield et al, 1996) and caudal type homeobox 2 (CDX2), a member of the caudal-related homeobox transcription factor gene family. CDX2 is a major regulator of intestine-specific genes involved in cell growth and differentiation (Gao et al, 2009).…”
Section: Results Hepcs Induced By Chir-99021 Possess Multilineage Difmentioning
confidence: 99%
“…Immunostaining was performed as previously reported [22,23]. The antibody details are described and listed in Supplementary Table S1.…”
Section: Immunostainingmentioning
confidence: 99%
“…Therefore, in vitro differentiation strategies employ a combination of small molecules or recombinant proteins to turn on or off these pathways at specific stages of the protocol [8,22]. Multiple groups have differentiated hPSCs to PDX1 and NKX6.1 co-expressing pancreatic progenitors in monolayer cultures [16,23], yielding even up to 90% of PDX1+/NKX6.1+ co-positive pancreatic progenitors [24,25] (Figure 3). Prior to the most recent improvements in protocols employing monolayer method, studies showed that cellular aggregation during differentiation process could improve the efficiency of pancreatic progenitors as compared to monolayer cultures [19,26].…”
Section: Generation Of Pancreatic Progenitors and Beta Cells From Hummentioning
confidence: 99%
“…Recently, Aigha et al has generated a novel population of pancreatic progenitor population expressing NKX6.1 in the absence of PDX1 (PDX1-/NKX6.1+) from hPSCs. The initial characterization of this population indicates the potential of PDX1-/NKX6.1+ cells to generate islet endocrine cells [25]. In vitro expanded islets undergoing de-differentiation have been shown to generate INS+ beta cells on extended culture [38,39], as well as progenitor cells with high aldehyde dehydrogenase activity extracted from the fetal and adult pancreas [40,41].…”
Section: Generation Of Pancreatic Progenitors and Beta Cells From Hummentioning
confidence: 99%